Quality of Life and General Well-being in People Receiving Hemodialysis Treatment: A Cross-sectional Study - Ali Alshraifeen; Sami Al-Rawashdeh; Mohammad Rababa (Jordan University of Science and Technology, 2023)
Background: End-stage renal disease (ESRD) and hemodialysis (HD) treatment are debilitating and progressive and can have a significant impact on patients’ general well-being and quality of life. Understanding the impact of ESRD and HD on Jordanian patients may help health care providers improve the type of care delivered. Objectives: this study aimed to examine quality of life (QOL) and general well-being (GWB) of patients undergoing HD treatment and to examine the associations between patients' demographic variables and QOL and GWB. Methods: this was a cross-sectional study in which 203 patients were recruited from different dialysis units across Jordan. Valid questionnaires were used to collect data on QOL and GWB along with demographic data sheet were used. Results:  participants scored moderately low on general well-being (GWB) with the highest means were for the Social Dysfunction and the Depression subscales, respectively. The highest reported score was on the Social Relationships domain of quality of life (QOL) and the lowest was for the Physical domain. Age groups significantly differed in their scores of GWB and in all domains of QOL apart from the Environmental domain. Female participants had a significantly higher (worse) difference than males in terms of the Somatic symptoms and Depression subscales of GWB. Conclusions and Implications to nursing: It was shown that HD treatment negatively influence patients QOL and GWB and interfere with their day-to-day lives. Dialysis nurses play a vital role in monitoring and supporting their patients and might provide an avenue by which they can optimize patients’ QOL and GWB. Hence, working with patients to find the best possible plan of care may have a positive impact on patients’ lives and health outcomes.